165k views
0 votes
Find the sum of the series Summation from n equals 1 to infinity (StartFraction 3 Over StartRoot n plus 2 EndRoot EndFraction minus StartFraction 3 Over StartRoot n plus 3 EndRoot EndFraction ).

1 Answer

4 votes

Looks like the series is supposed to be


\displaystyle\sum_(n=1)^\infty\frac3{√(n+2)}-\frac3{√(n+3)}

The series telescopes; consider the
kth partial sum of the series,


S_k=\displaystyle\sum_(n=1)^k\frac3{√(n+2)}-\frac3{√(n+3)}


S_k=\displaystyle\left(\frac3{\sqrt3}-\frac32\right)+\left(\frac32-\frac3{\sqrt5}\right)+\cdots+\left(\frac3{√(k+1)}-\frac3{√(k+2)}\right)+\left(\frac3{√(k+2)}-\frac3{√(k+3)}\right)


\implies S_k=\frac3{\sqrt3}-\frac3{√(k+3)}

As
k\to\infty, the second term converges to 0, leaving us with


\displaystyle\sum_(n=1)^\infty\frac3{√(n+2)}-\frac3{√(n+3)}=\frac3{\sqrt3}=\boxed{\sqrt3}}

User JOSEFtw
by
6.0k points